Design and Experiment of Quantitative Seed Feeding Wheel of Air-Assisted High-Speed Precision Seed Metering Device - Xiaojun Gao; Pengfei Zhao; Jiang Li; Yang Xu; Yuxiang Huang; Long Wang (Agriculture, 2022)
Aiming to solve the problems of the poor uniformity of seed flow discharge and serious damage of traditional straight grooved wheels to improve the performance of air-assisted maize high-speed precision seed metering devices, a staggering symmetrical spiral grooved feeding wheel with maize seeds was designed. To explore the influence of the spiral groove inclination angle and the length of the staggered symmetrical spiral groove feed wheel on the uniformity of seed flow discharge, the spiral groove length l and the spiral groove inclination angle ρ were used as the experimental factors, and the variation coefficient of the increase in seed, a full-factor simulation test was carried out for the test indicators, and it was found that both the inclination angle and the length of the spiral groove have an influence on the uniformity of seed flow discharge, and the influence of the inclination angle of the groove is more significant. Comparing the force of a single seed in the traditional straight grooved wheel and that of the spiral feeding wheel, it is found that the staggered symmetrical spiral grooved feeding wheel can reduce the damage of seed fertilizer. Through a bench test, the spiral groove length was found to be 50 mm, and the groove inclination angles are 30°, 45° and 90°. The test results show the variation trend and simulation results of the fluctuating coefficient of variation of the seed flow discharge in the bench test. The trend of change is basically the same. The inclination angle of the spiral groove is 45° and the uniformity of seed flow discharge is the best when the groove length is 50 mm, indicating that this structure can effectively improve the uniformity of material discharge, and the variation coefficient of seed flow discharge fluctuation is 3.12% and the seed breakage rate is 0.69%. Through the seeding performance test, it is verified that the staggered symmetrical spiral grooved feeding wheel can improve the seeding performance of the pneumatic high-speed precision metering device. When the metering device runs smoothly, the qualified rate reaches more than 90%, and the leakage rate is reduced to 0%. Therefore, the results of this study can provide a reference for research on uniform seeding, drill seeding and the uniform application of granular fertilizer.